Analisis Partisipasi Politik Warga Desa Suru dalam Pelaksanaan Pilkada Kabupaten Mojokerto Tahun 2024 - annas, Latifatul; Hasan Afandi, Ahmad; Rinayuhani, Tri Ratna (Universitas Islam Majapahit, Indonesia, 2025)
This study aims to analyze the level of community participation in Suru Village in the 2024 Regional Head Election (Pilkada) and identify influencing factors. Pilkada is the primary means of realizing popular sovereignty at the local level and an important indicator in measuring the quality of democracy. The research method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results indicate that community participation in Suru Village is high and active, with voter turnout exceeding 90%. Community involvement occurred at all stages: preparation, outreach, implementation, and evaluation. The main factors influencing participation include political awareness, understanding of rights and obligations as citizens, and support from the village government and community leaders. However, several challenges were also identified, such as participation remaining procedural and indications of small-scale transactional politics. This study recommends improving political education and election monitoring to strengthen the quality of democracy at the village level.